To the 210th Anniversary of Kharkiv University. The Personality of V. N. Karazin: the Attempt of Psychobiographical Research - Vovk, О. (Psychiatry, Neurology and Medical Psychology, 1970)
The article presents the results of the psychobiographical analysis of the life and activities the famous public figure, inventor, scientist and founder of Kharkiv University Vasyl’ Karazin (1773–1842). The main development Ukrainian and world trends of psychobiographical studies were characterized. The most revealing episodes of the biography of Vasyl’ Karazin were described. Further these incidents were compared with the typological scheme of personality research «Myers–Briggs Type Indicator» (MBTI). The hypothesis that Vasyl’ Karazin might have been the type ENTP («Inventor») was put forward.